Multitemporal land use and occupacion and morphometric analysis of the Aranha Stream watershed in Itapeva-SP - Siqueira, Henrique de Carvalho; Lima, César Gustavo da Rocha (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
From the beginning of the last century to the present day, Brazil has had a great migration of people from rural to urban areas. It resulted, many times, in a disorderly growth of cities and occupation of potentially floodable areas, which with the waterproofing of the soil potentiated such effects and, with the constant expansion of urban areas, tends to increase extreme events. The objective of the present work was to analyze the evolution of land use and occupation between the years 1991 and 2020, in addition to studying the morphometric parameters of the Aranha Stream watershed, in the municipality of Itapeva-SP. These analyzes were carried out with the aid of LANDSAT5 and LANDSAT8 satellite images, in addition to the SRTM digital elevation model, using the SPRING 5.4.3 software. The results indicated a growth of about 88% in the urban area within the basin throughout the study period, with a large part of this expansion in an area where floods were already observed, in the channeled part from the watercourse. Finally, the results from the morphometric analysis also showed medium to low tendencies to natural floods.